The Characterization of Biodiversity and Soil Emission Activity of the “Ladoga” Carbon-Monitoring Site - Evgeny Abakumov; Timur Nizamutdinov; Darya Zhemchueva; Azamat Suleymanov; Evgeny Shevchenko; Elena Koptseva; Anastasiia Kimeklis; Vyacheslav Polyakov; Evgenia Novikova; Grigory Gladkov; Evgeny Andronov (MDPI AG, 2024)
The global climate crisis forces mankind to develop carbon storage technologies. “Ladoga” carbon monitoring site is part of the Russian climate project “Carbon Supersites”, which aims to develop methods and technologies to control the balance of greenhouse gases in various ecosystems. This article shows the condition of soil and vegetation cover of the carbon polygon “Ladoga” using the example of a typical southern taiga ecosystem in the Leningrad region (Russia). It is revealed that soils here are significantly disturbed as a result of agrogenic impact, and the vegetation cover changes under the influence of anthropogenic activity. It has been found that a considerable amount of carbon is deposited in the soils of the carbon polygon; its significant part is accumulated in peat soils (60.0 ± 19.8 kg × m −2 for 0–100 cm layer). In agrogenically disturbed and pristine soils, carbon stocks are equal to 12.8 ± 2.9 kg × m −2 and 8.3 ± 1.3 kg × m −2 in the 0–100 cm layer, respectively. Stocks of potentially mineralizable organic matter (0–10 cm) in peat soils are 0.48 ± 0.01 kg × m −2 in pristine soils, it is 0.58 ± 0.06 kg × m −2 . Peat soils are characterized by a higher intensity of carbon mineralization 9.2 ± 0.1 mg × 100 g −1 × day −1 with greater stability. Carbon in pristine soils is mineralized with a lower rate—2.5 ± 0.2 mg × 100 g −1 × day −1 . The study of microbial diversity of soils revealed that the dominant phyla of microorganisms are Actinobacteria , Bacteroidetes , and Proteobacteria however, methane-producing Archaea— Euryarchaeota —were found in peat soils, indicating their potentially greater emission activity. The results of this work will be useful for decision makers and can be used as a reference for estimating the carbon balance of the Leningrad region and southern taiga boreal ecosystems of the Karelian Isthmus.